Preparation and Characterization of New Oxide Ion Conductors in Bi2O3-As2O5 System - Lee, S. L.; Lee, C. K.; Sinclair, D. C.; Chong, F. K.; Halim, S. A.; Yap, T. (Institut Kimia Malaysia, 2005)
Materials in xBi2O3-As2O5 binary system: 1 < x < 7, were prepared by solid state reaction. XRD shows that single phase materials were formed when x = 5, 5.5, 5.667, 5.75, 6 and 7. The symmetry and space group of the materials were determined. Compositions with 5 < x < 6.25 are solid solutions. Electrical properties of the single phase materials were studied using ac impedance spectroscopy at a frequency range of 10 Hz to 13 MHz. These materials are thermally stable and appear to be oxide ion conductors. Highest conductivity was obtained in Bi23As4O44.5 with s value of 5.66 x 10-5 ohm-1 cm-1, Ea = 0.72 eV at 300oC.